PENDAMPINGAN IBU DALAM MENINGKATKAN POLA ASUH NUTRISI PADA BALITA YANG MENGALAMI GIZI KURANG - ULVA NOVIANA; Heni Ekawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Nutritional care is a food intake to support physical and biological growth and development, toddlers in an appropriate and balanced pattern of child care in the form of behavior of mothers or other caregivers in terms of proximity to children, providing food, caring, hygiene, giving love and so on. Based on a preliminary study of in the village of Camplong data obtained from 10 there were 7 (70%) mothers did not play a good role in improving nutrition parenting in infants, there were 3 (30%) mothers had a good role in improving nutrition parenting in infants, the purpose of the study is to analyze maternal assistance in improving nutritional care for toddlers who are suffering from malnutrition This research used Quasy Experiment Design with two group pre-test-post test design approach. The independent variable was mother's assistance while the dependent variable was Nutritional care in toddlers who experience malnutrition. Total population of 26 mothers who have undernourished infants with 13 samples of the treatment group and 13 control group mothers taken by simple random sampling. This research was conducted in the Camplong public Health Center in March 2020 and tested statistically using the Wilcoxon test with a = 001. This research used Quasy Experiment Design with two group pre-test-post test design approach. The independent variable was mother's assistance while the dependent variable was Nutritional care in toddlers who experience malnutrition. Total population of 26 mothers who have undernourished infants with 13 samples of the treatment group and 13 control group mothers taken by simple random sampling. This research was conducted in the Camplong public Health Center in March 2020 and tested statistically using the Wilcoxon test with a = 001. The results of this study found that toddlers who experienced undernutrition after being given assistance obtained an increase in nutritional care for mothers by 13 mothers (100%). Based on the Wilcoxon statistical test an increase in nutrition parenting showed that p value = 001, so that it can be concluded that there was an effect of maternal assistance in improving nutritional care for toddlers who experience malnutrition in the working area of the Camplong Sampang Public health center. It is recommended to mothers to improve nutrition in their toddlers by providing nutritious toddlers with nutritious food according to their needs, attention to processing, serving, types of foods suitable for toddlers to improve the nutritional status of toddlers, especially in toddlers who experience undernourished nutrition.